Deposition and characterization of germanium nitride film using different thermal nitridation temperature / Low Yan Jie - Low , Yan Jie (2018)
This study is aimed at investigating the effect of thermal nitridation temperature on the growth of germanium nitride (?-Ge3N4) thin film and its effectiveness as a buffer layer to suppress the growth of unwanted germanium oxide (GeO2) interfacial layer. The ?-Ge3N4 films were grown on germanium substrate (Ge) by thermally nitriding Ge with nitrogen (N2) gas purging for 15 minutes at 400, 500 and 600°C. The temperature dependence of the growth of ?-Ge3N4 films under pure N2 gas purge was studied profoundly through X-ray diffraction (XRD) and Fourier transform infrared (FTIR) characterization. The physical, chemical and compositional properties of 400, 500 and 600°C thermally nitrided Ge samples were analyzed through the resulting XRD and FTIR spectra. The resulting XRD spectra give information on the intensity of ?-Ge3N4 and t-GeO2 phases, microstrain embedded in each phase, and crystallite size of the phases by means of Debye-Scherrer equation and Williamson-Hall (W-H) analysis. The intensities of ?-Ge3N4 phases were found to first increase from 400°C and reach a peak at 500°C, gradually declining thereafter at 600°C. This suggests that the optimum growth of ?-Ge3N4 phases is at 500°C as the ?-Ge3N4 phases are appeared to be unstable at 400 and 600°C. The ?-Ge3N4 was determined to exhibit the largest crystallite size and highly homogeneous size distribution at 500°C indicating the highly uniform growth rate at 500°C. Tensile microstrain embedded in ?-Ge3N4 layer was only observed at the highest growth rate temperature, 500°C. The tensile microstrain indicates the ?-Ge3N4 phase islands has grown into a uniform film by forming grain boundary. The compressive microstrain in 400 and 600°C ?-Ge3N4 layer was expected to be attributed to the disruption of ?-Ge3N4 thin film growth by formation of t-GeO2. Based on the FTIR results, the 500°C nitrided sample was found to have a substantial number of Ge-N characteristic peaks consecutively over the wavenumber range of 400 to 1300 cm-1 and a very small number of low intensity peaks which are indicative of Ge-O bond. Unlike 500°C nitrided sample, relatively high intensity peaks of Ge-O bond are observed in the spectra of 400 and 600°C nitrided samples. Broadly translated, the result findings indicate 500°C as the optimal thermal nitridation temperature of ?-Ge3N4 thin film growth.